Design of Natural Deep Eutectic Solvents for the Ultrasound-Assisted Extraction of Hydroxytyrosol from Olive Leaves Supported by Cosmo-Rs - Zuniga-Navarro, G; Romero-Figueroa, J; Quijada-Maldonado, E; Merlet-Venturelli, G; Cabezas-Cornejo, R; Villarroel-Utreras, E (Elsevier B.V., 2020)
The main aim of this work was the design of natural deep eutectic solvents (NADES) for the extraction of hydroxytyrosol (HT) from olive leaves. This design was supported by COSMOS-RS screening and compared with the experimental results. For which, eight NADES (four sugar-based and four organic acid-based NADES) were prepared. The experiments for the HT ultrasound-assisted solid–liquid extractions (UAE) were done in a 1:4 solid-to-solvent ratio for 24 hrs, and the COSMO-RS optimization and analysis of each eutectic mixture was modelled as a single molecule, with both HBD and HBA species joined by the hydrogen bond. The experimental results showed that the citric acid:glycine:water (2:1:1) eutectic mixture reached values of 87 ppm of HT, more than four times higher than the values obtained with water, the conventional solvent used for the extractions of polyphenols. On the other hand, these values were contrasted with the calculations of the activity coefficient at infinite dilution and the sigma profile delivered by COSMO-RS, concluding that this tool can be used to predict the behaviour of deep eutectic solvents with HT. These experimental and theoretical results allowed to generate a high-concentration HT extract in a stable and GRAS NADES phase. Additionally, the utilization of a cellulases-based enzymatic pre-treatment prior to the UAE, could be an effective method to obtain higher extraction values of HT. © 2020 Elsevier B.V.